Predictors of 1‐year visual outcome in neovascular age‐related macular degeneration following intravitreal ranibizumab treatment. (19th October 2011) - Bloch, Sara B.; la Cour, Morten; Sander, Birgit; Hansen, Louise K. H.; Fuchs, Josefine; Lund‐Andersen, Henrik; Larsen, Michael
Abstract. Purpose: To describe predictors of visual outcome in patients treated with intravitreal ranibizumab for choroidal neovascularisation (CNV) in age‐related macular degeneration (AMD). Methods: Retrospective review of 279 patients with CNV in AMD who fulfilled MARINA/ANCHOR study eligibility criteria and were treated with repeated intravitreal injections of ranibizumab 0.5 mg in routine clinical practice, beginning with three initial injections at 4‐week intervals followed by individualized retreatment for the subsequent 9 months. Study parameters included best‐corrected visual acuity (BCVA) and morphological characteristics. Results: Mean BCVA relative to baseline was +4.7 (p < 0.0001), +4.2 (p < 0.0001)and −0.4 (p > 0.667) Early Treatment Diabetic Retinopathy Study letters after 3, 6 and 12 months, respectively, after a mean of 5.1 injections when the proportion of patients with BCVA ≥70 letters had doubled compared with baseline. Predictive factors for BCVA ≤35 letters after 12 months were BCVA ≤35 letters at baseline and month 3 (p < 0.0001) while BCVA ≥70 letters at month 12 was associated with BCVA ≥70 letters at baseline and month 3 (p < 0.001) and with total lesion size <4 DA (p = 0.0147). Conclusion: Under a ranibizumab regimen with substantially fewer injections than with fixed four‐weekly injection regimens, BCVA was improved compared with the natural history of neovascular AMD, but did not achieve the visual gain observed in randomized clinical trials using fixed 4‐week retreatment. Visual acuity at month 3, after the initial fixed‐interval injections, was the strongest predictor of BCVA at month 12.